Analisis Kesiapan Guru Mata Pelajaran Bahasa Arab dalam Implementasi Kurikulum Merdeka di MI Islamiyah Banin Senori - Afida, Febrian Nafisa Nurul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2023)
The independent curriculum complements the previous curriculum, which serves as a solution to the problem of learning loss resulting from the impact of the COVID-19 disaster. Present as a curriculum that drives results from the Ministry of Education. This research aims to determine the readiness of Arabic language subject teachers in implementing the independent curriculum. The type of research that researchers use is descriptive qualitative. The research subject is an Arabic language subject teacher in class 1 of MI Islamiyah Banin. The data collection technique was by asking questions to Arabic language subject teachers at MI Islamiyah Banin regarding teacher readiness in implementing the independent curriculum. To identify the readiness of Arabic language subject teachers at MI Islamiyah Banin to implement the independent curriculum was expressed using a questionnaire consisting of 6 indicators, namely: 1) understanding of the curriculum structure, 2) readiness of learning plans, 3) readiness of the learning process 4) readiness of teaching modules, 5) readiness of facilities and infrastructure, 6) readiness for learning assessment. The results of the research show that the readiness of teachers to implement the independent curriculum in the Arabic language subject is based on the 6 indicators that the author has proposed to the Arabic language subject teachers. This shows that the readiness of Arabic language teachers to implement the independent curriculum in the Arabic language subject is still not very high because they still don't really understand the independent curriculum as a whole, both in curriculum structure, planning, teaching materials, and assessments.